Optimization of MW dispatch among distributed energy resources - Goh, Wen Pu. (2009)
Optimization of MW Dispatch among Distributed Energy Resources is a continuation project from 2007/08 semester 2, FYP A1122: MW optimization of intelligent energy distribution system. The project involves building a small distributed generation system with a program that monitors and controls the operation of the system.